2017
DOI: 10.1007/s12070-017-1134-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Outcome of Stapes Surgery

Abstract: To study the outcome of stapes surgery based on the Clinical, Audiometry, and Surgical pre- and postoperative factors. This study is a prospective study of factors affecting the outcome of stapes surgery in otosclerosis patients. From February 2010 to June 2011, 57 patients of confirmed clinical otosclerosis were analysed. Out of them, 31 patients were included in our study as were available for follow-up. Clinical, audiometry and surgery-related parameters were included to assess the surgery outcome. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
8
3
Order By: Relevance
“…In our study, 93.6% of the patients had ABG closure 10 dB in primary surgery. According to previous research, 7,9,[14][15][16] an ABG 10 dB was seen in 62% to 94% of the patients. Differences in the number of studied patients, the applied surgical technique (e.g., stapedotomy, reverse stapedotomy, stapedectomy, and laser-assisted procedures) and the surgeon's experience 17 noticed the existence of a learning curve in stapes surgery.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our study, 93.6% of the patients had ABG closure 10 dB in primary surgery. According to previous research, 7,9,[14][15][16] an ABG 10 dB was seen in 62% to 94% of the patients. Differences in the number of studied patients, the applied surgical technique (e.g., stapedotomy, reverse stapedotomy, stapedectomy, and laser-assisted procedures) and the surgeon's experience 17 noticed the existence of a learning curve in stapes surgery.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, 2.6% of the cases had obliterative footplate. Shah and Ganapathy and Hausler reported the condition to have an incidence rate of 3% to 10%. Similar to previous studies, we found significantly worse ABG closure in patients with obliterative footplate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, the use of connective tissue seal may prevent perilymph leakage and restore the stiffness of the annular ligament. In this study, soft tissue from postauricular sulcus was used, whereas Shah et al 31 used absorbable gelatin sponge or fat as a sealing material.…”
Section: Discussionmentioning
confidence: 99%